The Constructive Function Of Play In The Development Of Thinking - Shoira Kubaeva (Periodica Journal, 2026)
This article examines the constructive function of play in the development of human thinking. Play is analyzed not merely as an entertaining activity, but as a fundamental cognitive and sociocultural mechanism that shapes intellectual abilities, creativity, and problem-solving skills. The study explores philosophical and psychological approaches to understanding play as a form of meaningful activity that contributes to the formation of logical reasoning, imagination, and reflective thinking. Special attention is given to the role of play in educational processes and its impact on the development of independent and critical thinking in learners. The research highlights that play serves as a constructive environment where individuals model reality, experiment with possibilities, and internalize social and intellectual norms. The article concludes that integrating play-based methods into modern educational practice enhances cognitive development and supports the formation of an active, innovative, and adaptable personality.
Keywords: Play; thinking development; constructive function; cognitive activity